Signal peptide peptidase‐like 2c impairs vesicular transport and cleaves SNARE proteins. (6th May 2019) - Papadopoulou, Alkmini A; Müller, Stephan A; Mentrup, Torben; Shmueli, Merav D; Niemeyer, Johannes; Haug‐Kröper, Martina; von Blume, Julia; Mayerhofer, Artur; Feederle, Regina; Schröder, Bernd; Lichtenthaler, Stefan F; Fluhrer, Regina
Abstract :